2018
DOI: 10.4103/1793-5482.181133
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric isolated cortical (Ectopic) anaplastic ependymoma

Abstract: Ependymomas are tumors derived from ependymal cells lining the ventricles or from the central canal of the spinal cord. It usually arises in the ventricles with extra ventricular extension. Less than 15 cases of purely cortical ependymomas are reported. We report a rare case of purely cortical anaplastic ependymoma in a pediatric patient, which is rarely reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Ependymomas recur more frequently in the initial location after local failure. Kharosekar et al ( 15 ) believed that if the tumor was completely located in the cortex, the patient might have a better prognosis. And, Saito et al ( 16 ) reported that anaplastic ependymomas can disseminate within the central nervous system without local failure.…”
Section: Discussionmentioning
confidence: 99%
“…Ependymomas recur more frequently in the initial location after local failure. Kharosekar et al ( 15 ) believed that if the tumor was completely located in the cortex, the patient might have a better prognosis. And, Saito et al ( 16 ) reported that anaplastic ependymomas can disseminate within the central nervous system without local failure.…”
Section: Discussionmentioning
confidence: 99%